2022
DOI: 10.2176/jns-nmc.2021-0313
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Progression of Diffuse Low-grade Gliomas: A Systematic Review and Meta-analysis on Incidence and Related Factors

Abstract: Malignant progression of diffuse low-grade glioma (LGG) is a critical event affecting patient survival; however, the incidence and related factors have been inconsistent in literature. According to the PRISMA guidelines, we systematically reviewed articles from 2009, meta-analyzed the incidence of malignant progression, and clarified factors related to the transformation. Forty-one articles were included in this study (n = 7,122; n, number of patients). We identified two definitions of malignant progression: h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…For example, IDH wildtype was identified by Satar et al, 3 as a postoperative maker of MT in LGG patients. However, according to the latest WHO CNS classification scheme, 2 tumors with wildtype IDH are currently The potential predictive markers of MT in LGG have been widely investigated, 3,5 with several factors such as older age, 8,29 male sex, 4,8 tumor size, 4,10 chemotherapy, 4,6,8,30,31 radiotherapy, 31 and EOR, 8,10,26 as well as various biomarkers, including CDC20, 32 BIRC3, 33 CX3CR1, 34 FGL2. 35 However, this study identified independent predictors of MT as 1p/19q codeletion, radiotherapy, EOR, Ki-67 index, and KPS score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, IDH wildtype was identified by Satar et al, 3 as a postoperative maker of MT in LGG patients. However, according to the latest WHO CNS classification scheme, 2 tumors with wildtype IDH are currently The potential predictive markers of MT in LGG have been widely investigated, 3,5 with several factors such as older age, 8,29 male sex, 4,8 tumor size, 4,10 chemotherapy, 4,6,8,30,31 radiotherapy, 31 and EOR, 8,10,26 as well as various biomarkers, including CDC20, 32 BIRC3, 33 CX3CR1, 34 FGL2. 35 However, this study identified independent predictors of MT as 1p/19q codeletion, radiotherapy, EOR, Ki-67 index, and KPS score.…”
Section: Discussionmentioning
confidence: 99%
“…Despite aggressive treatments, malignant transformation (MT) appears to be an inevitable event for patients with LGG 3,4 . Previous studies have denoted that LGG after a long‐term of follow‐up would ultimately progress to a high‐grade variant, including grade 3 and 4, both of which were defined as MT 3,5 . Early detection of indicators of MT is crucial for treatment decision‐making because of the unpredictable course of MT 3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was identified as grades II and III brain tumors by the World Health Organization. The incidence is estimated to be approximately 0.8 cases per 100,000 population (Nakasu and Nakasu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytoma, isocitrate dehydrogenase (IDH)-mutant (A_IDH_mut) and oligodendroglioma, IDH-mutant and 1p/19q-codeleted (O_IDH_mut) are the 2nd and 3rd most common diffuse infiltrating gliomas in adults after glioblastoma, IDH-wildtype (GBM). According to a meta-analysis, the 10-year progression-free survival (PFS) rates of O_IDH_mut and A_IDH_mut are 62.5% ~ 71.7% and 30.4% ~ 38.3%, respectively 1 . The genomic and molecular alterations of IDH_mut oligodendroglioma and IDH_mut astrocytoma were well described by The Cancer Genome Atlas in 2015 and Ceccarelli et al in 2017 2 , 3 and introduced in neuropathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%